2020
DOI: 10.1021/acs.molpharmaceut.0c00747
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization Reveals the Significance of Rare Coding Variations in Human Organic Anion Transporting Polypeptide 2B1 (SLCO2B1)

Abstract: The organic anion transporting polypeptide 2B1 (OATP2B1), which is encoded by the SLCO2B1 gene, plays important roles in the absorption and disposition of its substrate drugs. Nonsynonymous variations of SLCO2B1 change its amino acid sequence and may alter its function. However, so far, very few genetic variants of SLCO2B1 have been functionally characterized.In the present study, first of all, 14 nonsynonymous single nucleotide variants (SNVs) of SLCO2B1 have been identified from the dbSNP database. Then, hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 60 publications
1
17
1
Order By: Relevance
“…Such a result would be in keeping with its low CADD/REVEL/MetaLR scores. However, our findings for the OATP2B1 c.935G>A variant contrast with others that find a reduction in transport function for some substrates ( Yang et al, 2011 ; Nies et al, 2013 ; Yang et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Such a result would be in keeping with its low CADD/REVEL/MetaLR scores. However, our findings for the OATP2B1 c.935G>A variant contrast with others that find a reduction in transport function for some substrates ( Yang et al, 2011 ; Nies et al, 2013 ; Yang et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, we found that the OATP2B1 c.1457C>T variant had reduced transport function in vitro which was similar to other studies (Nozawa et al, 2002;Nies et al, 2013). But in contrast, two other studies found increased activity of OATP2B1 c.1457C>T (Ho et al, 2006;Yang et al, 2020). Lastly, we found that the most common OATP2B1 variant, namely c.935G>A, had rather benign functional consequences for substrates, except for a very slight reduction in rosuvastatin transport activity.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations